DD-031 Shortage of anti-infectives and its consequences in a tertiary hospital. (14th February 2016) - Calvo, M; Sanabrias, R; Saavedra, V; Gonzalez, C; Escudero, B; Sanchez, A
Abstract : Background: Currently, drug shortages are becoming more common. The group of anti-infectives is one of the most affected, and may involve a reduction in pharmacotherapeutic efficacy and increased medication errors. Purpose: To analyse the impact of shortages of anti-infectives and to describe the different actions carried out by the pharmacy department. Material and methods: A prospective descriptive study was carried out from October 2014 to March 2015 in a tertiary hospital. The data collected were: affected drug, duration of the shortage and measures implemented. The data were obtained from the drug shortages list of the Spanish Agency for Medicines and Health Products (AEMPS) and discontinuations from the BOT plus programme. We included drugs from the J group of the Anatomical Therapeutic Chemical (ATC) classification system and anti-infectives included in other groups. Results: During the study period, there were 7 drugs affected by discontinuation of marketing and 6 with supply problems. The measures taken by pharmacist were as follows. For anti-infectives whose marketing was discontinued, the provider had to be changed in 71% (5) of cases; in another 14% (1) a different presentation to clinical packaging was used, and in the remaining 14% (1) a different dose presentation was used. The medicines involved were: amoxicillin/clavulanate 1 g/200 mg and 2 g/200 mg injections, cefepime 2 g injection, meropenem 1 g and 500 mg injections, rifampin 300 mg tablets and darunavir 300 mg capsules. The average duration of drugs shortages was 46 days (20–68). The strategies for the management were: Change the provider in 3 cases (50%): mupirocin 2% ointment, hepatitis A virus vaccine and azithromycin 500mg injection; Use a therapeutic alternative in 1 case (17%): cefuroxime 250 mg/5 mL oral solutions, the alternative drug was amoxicillin/clavulanate; No action taken due to its limited use and enough stock available in our pharmacy department in 2 cases (33%): rabies immunoglobulin injections and acyclovir 3% ophthalmic ointment. Conclusion: Shortages imply increased workload for hospital pharmacists due to the administrative formalities, determining of therapeutic alternatives with medical specialists in infectious diseases and the need to keep all healthcare providers informed, in order not to compromise continuity of therapy. References and/or Acknowledgements: Bot plus 2.0. Available at: http://www.portalfarma.com/inicio/botplus20/que-es-Bot-Plus/Paginas/default.aspx Agencia Española de Medicamentos y Productos Sanitarios. Available at: http://www.aemps.gob.es/ No conflict of interest.